2004
DOI: 10.1016/s1010-7940(03)00644-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of atrial fibrillation after cardiac valvular surgery by epicardial, biatrial synchronous pacing

Abstract: Temporary, biatrial synchronous pacing during the first 3 postoperative days is safe and has a significant rhythm-stabilizing effect in patients undergoing valvular cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…19 The usefulness of nonpharmacological strategies, such as continuous overdrive atrial pacing through temporary epicardial electrodes, is currently under investigation. 20 Beneficial effects of SNP in cardiac surgery have been reported in many studies. Massoudy et al 21 reported that administration of SNP (as an NO donor) for just the first 20 minutes of reperfusion to patients undergoing CABG led to a reduction of the acute inflammatory response, especially a reduction in levels of interleukin-6 and interleukin-8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The usefulness of nonpharmacological strategies, such as continuous overdrive atrial pacing through temporary epicardial electrodes, is currently under investigation. 20 Beneficial effects of SNP in cardiac surgery have been reported in many studies. Massoudy et al 21 reported that administration of SNP (as an NO donor) for just the first 20 minutes of reperfusion to patients undergoing CABG led to a reduction of the acute inflammatory response, especially a reduction in levels of interleukin-6 and interleukin-8.…”
Section: Discussionmentioning
confidence: 99%
“…NO production by SNP requires the presence of vascular tissue. 20 The aim of the present prospective, blinded, randomized study was to evaluate the usefulness of SNP in preventing AF in patients undergoing first elective CABG. Here, we present the results of a pilot study designed to evaluate the effectiveness of perioperative (during the rewarming period) SNP administration and discuss possible strategies by which SNP treatment can be beneficial to prevent postoperative AF.…”
Section: Editorial P 467 Clinical Perspective P 481mentioning
confidence: 99%
“…[20][21][22][23] Recently, several reports have shown that multisite temporary atrial pacing via epicardial electrodes placed during surgery might be effective in preventing postoperative AF. [24][25][26][27][28][29][30][31][32] In a double-blind, randomized study, Daoud et al evaluated the effects of different pacing modes in 118 patients who had undergone open heart surgery. 28 In this study, patients were randomized to one of the following three groups: right atrial pacing with an inhibited mode at a rate of 45 beats/min; right atrial overdrive pacing with a triggered mode ≥ 10 beats greater than the patient's intrinsic (but not < 85 beats/min) rate; and biatrial overdrive pacing with a triggered mode ≥ 10 beats greater than the patient's intrinsic (but not < 85 beats/min) rate.…”
Section: Discussionmentioning
confidence: 99%
“…La prophylaxie de la FA postopé ratoire par une stimulation synchrone bi-atriale a é té suggé ré e par quelques é tudes [9,10]. Toutefois, cette mé thode de pré vention n'a pas é té validé e, malgré qu'elle soit incluse dans les recommandations ACCP 2005.…”
Section: Synthè Se Des Donné Esunclassified